Lullaby Rite and Traditions of "Beshik Tuyi" of Surkhan Oasis - Khudaikulova Latifa Avazovna (International Journal on Integrated Education, 2022)
In the system of the genre of the traditional ritual folklore of the peoples of Central Asia, associated with the birth of a child, an important place is occupied by the first swaddling and lullaby festive ritual folklore. Beshik tuyi is considered one of the oldest components of the ritual folklore of the Turkic peoples. Consequently, verbal components, texts of a magical nature, which are the basis of ritual customs, are due to magical action associated with ancient historical ideas. The ancient tradition of folklore, associated in Uzbek folklore with the wedding of “beshik tuyi”, has been preserved in the Surkhandarya region and at present, although in the form of post-folklore, continues to live. During our scientific expedition, it turned out that such elements of ancient customs as “uyquchi” (“sleep”), “qurquv-quurquv” (“fear”), “sog bulsin” (“let it be healthy”) have survived to this day.